2006
DOI: 10.1111/j.1399-0012.2006.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of employment after liver transplantation

Abstract: Employment after orthotopic liver transplantation (OLT) indicates recipients' physical/psychosocial adjustment. Our aim was to determine clinical, socioeconomic and health-related quality of life parameters influencing employment after OLT. Questionnaire on demographics, medical conditions, alcohol and drug use before/after OLT, and a validated 12-Item Short Form Health Survey (SF-12) were mailed to 126 adult OLT patients. Stepwise logistic regression was conducted to identify best predictors of post-OLT emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
58
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 23 publications
8
58
1
1
Order By: Relevance
“…However, only 26 to 57% of recipients return to work (44,46,47). This wide range may depend on differing definitions of "employed," on use of non-validated instruments, and on disparity in patient population, sample size, and length of follow-up.…”
Section: Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only 26 to 57% of recipients return to work (44,46,47). This wide range may depend on differing definitions of "employed," on use of non-validated instruments, and on disparity in patient population, sample size, and length of follow-up.…”
Section: Employmentmentioning
confidence: 99%
“…This wide range may depend on differing definitions of "employed," on use of non-validated instruments, and on disparity in patient population, sample size, and length of follow-up. Proposed predictors of post-LT employment include younger age, pretransplant employment and high income, private insurance, absence of pretransplant diabetes, good physical functioning, and higher general health score (45)(46)(47).…”
Section: Employmentmentioning
confidence: 99%
“…The possibility to return to work after liver transplantation also depends on the type of work previously held (Loinaz et al, 1999;Sahota et al, 2006;Adams et al, 2006). Interestingly, despite the socio-cultural differences that could affect work patterns and perceptions of QOL, these same results were found among transplant recipients in Japan (Kita et al, 1996), Taiwan (Shih et al, 2000), Sweden (Hellgren et al, 1998) and the United States (Bravata et al, 2001).…”
Section: Employmentmentioning
confidence: 99%
“…42,45,47 On the other hand, transplant recipients who worked prior to transplantation and have higher pre-transplant incomes and levels of education, as well as those without diabetes and receiving the kidney from the living donor are more likely to return to work. 42,46 It has been reported that solid organ transplant recipients who return to work differ in several aspects from those who do not, including shorter periods of pre-transplant disability and unemployment (age 35-50 years), higher educational level, retention of health insurance, and a professional job. 43 Furthermore, post-transplant employment is associated with better transplant outcome.…”
Section: Employment Statusmentioning
confidence: 99%
“…Employment rates after solid organ transplantation have been reported as low as 45-55% [42][43][44][45][46] driven by poor health, acute rejection episodes, and fear of loss of health insurance or disability benefits. 42,45,47 On the other hand, transplant recipients who worked prior to transplantation and have higher pre-transplant incomes and levels of education, as well as those without diabetes and receiving the kidney from the living donor are more likely to return to work.…”
Section: Employment Statusmentioning
confidence: 99%